PERMOHONAN HAK MILIK YANG BERASAL DARI TANAH NEGARA DI KANTOR PERTANAHAN KOTA SEMARANG - Ilham Ilham; Djauhari Djauhari (Jurnal Akta, 2017)
The basic foundation for the government and the people of Indonesia to formulate the politics of law and the policy of land affairs has been contained in the 1945 Constitution of the Republic of Indonesia Article 33 paragraph (3) which "earth, water and natural resources contained therein are controlled by the state and Used for the greatest prosperity of the people ". The problems in this research are: 1) Why is the request of Hak Milik coming from state land need a very long time? 2) What is the procedure or procedure of certifying Land Ownership from the State in Land Office of Semarang City? 3) What are the obstacles that arise in the process of granting Land title certificate that has been given by the state in the Land Office of Semarang City and how is the solution of the barriers?The approach method used in this research is sosiologis juridical approach method using qualitative descriptive data analysis method.The results of the research show as follows: 1) The application of the right to property derived from state land takes a very long time, In the petition contains information about the applicant, the description of his land which includes juridical data and physical data and other information in the form of information about the number of fields, And the status of the land owned by the applicant including the requested plot of land and any other information deemed necessary. 2) Procedures or procedures for granting land title certificate originating from the state in the Land Office of Semarang City, Rights Application, Applicant of land title certificate shall be divided into 4 categories: Right Receiver, Heirs, Land Owners, Owner of Land Rights Certificate Lost or damaged, Measurement and Registration of Rights, After the completion of the application file is filed and submitted to the Land Office, the subsequent process in the land office shall be the measurement, mapping and registration of its right, issuance of the Certificate, that the Land Rights Application is a process, The entry of the petition to the competent authority until the birth of the requested land. Before the land rights application enters the authorized institution, there is a process of preparation.Keywords: Right of Ownership, State Land, Land Office of Semarang City